Developing Socio-Emotional Intelligence in Higher Education Scholars - Devis-Rozental, Camila (Springer International Publishing, 2018)
This book explores the impact of socio-emotional intelligence on wellbeing in higher education. Stemming from years of investigation and educational expertise with trainee teachers and academics, the book identifies ways in which socio-emotional intelligence can be developed in university environments. The author begins by analysing the concept of socio-emotional intelligence and its development, before confronting distinctive areas for improvement within the context of teaching and learning in higher education. The book explores the importance of understanding and labelling emotions, and how opportunities for self-reflection arise through an environment that meets practical needs. The author contends that support from other scholars is vital to the development of socio-emotional intelligence. The book concludes with a set of practical suggestions for promoting personal development. It will be a valuable resourse for anyone working in higher education who is interested in improving their own wellbeing and that of those around them. .